Genetic investigation of the origin of an allograft ureteral carcinoma with short tandem repeats: From recipient or donor? - Jia-Yuh Sheu; Jeff Shih-Chieh Chueh; Chao-Yuan Huang; Hsiao-Lin Hwa; Shuo-Meng Wang (Urological Science, 2023)
Purpose: The purpose of this study was to demonstrate the usefulness of genetic analysis with short tandem repeats (STRs) to identify the cellular origin of an unusual allograft urothelial carcinoma (UC). Materials and Methods: A 30-year-old Taiwanese woman received a kidney transplant from her aunt in 2000. She was diagnosed with high-grade UC of her native upper urinary tract (urinary tract UC [UTUC]) in 2012. During a follow-up, tumors were discovered in both her native right ureter and graft ureter. The final pathology report identified this as a high-grade invasive UC. To investigate the origin of her allograft ureteral cancer to determine whether it originated from her own or the donor cells, we employed STR analysis because the recipient and donor were of the same gender. Results: We compared 23 autosomal STR loci and one amelogenin. Overall, the STR expression from the native right UTUC was identical to that of the recipient's buccal cells. The STR expression of the graft UTUC was similar to that of recipient cells, but importantly, some STR loci showed gene expressions that were only present in the donor's buccal cells. Conclusion: We concluded that the native right UTUC was of recipient origin and not metastatic from the donor. While we cannot be entirely sure of the tumor origin of the graft ureteral UC, we conjectured that it was not wholly from the donor source alone; either because of the intermixing with the donor stroma or due to microchimerism that developed after transplantation.